Modeling of bioethanol production through glucose fermentation using Saccharomyces cerevisiae immobilized on sodium alginate beads. Issue 1 (31st December 2022) - Damayanti, Astrilia; Bahlawan, Zuhriyan Ash Shiddieqy; Kumoro, Andri Cahyo
Abstract: As a response to the increasing demand for ethanol as a renewable energy source, the design of a bioreactor to facilitate efficient glucose fermentation by Saccharomyces cerevisiae is very essential. Although a number of mathem atical models that gave some parameters used for bioreactor design can be found in the literature, only a few models were designated for fermentation using immobilized S. cerevisiae . This study aimed to develop an unstructured fermentation kinetics model based on the mass transfer phenomena and the Monod equation to describe the rate of glucose consumption, glucose concentration on the bead surface, yeast cell growth, and ethanol concentration. Four ordinary differential equations obtained from the model development were solved simultaneously using fourth order Runge-Kutta with the help of MATLAB software. The accuracy of the model was verified with the experimental data collected from the relevant literature with the average error (%) of the variation of loading yeast mass, pH, and temperature were 5.12–10.08, 3.63–7.95, and 5.35–11.87, respectively. Seven adjustable kinetic parameters were also successfully obtained for a quantitative description of bioethanol production from fermentation of glucose employing S. cerevisiae immobilized on sodium alginate beads. The simulation results proved that the proposed model can accurately predict the concentration of glucose and ethanol in the fermentation broth, concentration of glucose on the alginate beads surface, and yeast cell concentration. Hence, the model can be potentially applied for the design of a larger scale batch bioreactor for glucose fermentation using S. cerevisiae immobilized on sodium alginate beads for ethanol production.